Reconfiguring the natures of childhood - Taylor, Affrica (Milton Park, Abingdon, Oxon : Routledge, 2013)
"In this fascinating new book, Affrica Taylor encourages an exciting paradigmatic shift in the ways in which childhood and nature are conceived and pedagogically deployed, and invites readers to critically reassess the naturalist childhood discourses that are rife within popular culture and early years education.Through adopting a common worlds framework, Reconfiguring the Natures of Childhood generates a number of complex and inclusive ways of seeing and representing the early years. It recasts childhood as:messy and implicated rather than pure and innocent; situated and differentiated rather than decontextualized and universal; entangled within real world relations rather than protected in a separate space.Throughout the book, the author follows an intelligent and innovative line of thought which challenges many pre-existing ideas about childhood. Drawing upon cross-disciplinary perspectives, and with international relevance, this book makes an important contribution to the field of childhood studies and early childhood education, and will be a valuable resource for scholars, postgraduate students and higher education teachers"--
pt. 1. The seduction of nature -- pt. 2. Reconfiguring the natures of childhood.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Early childhood education -- Philosophy; Philosophy of nature; Electronic books